1996
DOI: 10.1182/blood.v88.5.1813.bloodjournal8851813
|View full text |Cite
|
Sign up to set email alerts
|

ETO and AML1 phosphoproteins are expressed in CD34+ hematopoietic progenitors: implications for t(8;21) leukemogenesis and monitoring residual disease

Abstract: To study acute myelogenous leukemia 1 (AML1) transcription factor, ETO protein, and t(8;21) AML chimeric AML1/ ETO protein in normal hematopoiesis and in leukemia, we raised rabbit antisera to a bacterially expressed polypeptide containing amino acid residues 1 to 220 of ETO and to synthetic peptides extending from residues 528 to 548 of ETO and 32 to 50 of AML1. The latter was selected to have little chance of cross-reactivity with other members of the PEBP2 alpha family. With affinity-purified reagents, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…A), since they resemble normal HSCs (Engelhardt et al, ). As it has been described, low levels of endogenous Runx1 mRNA were observed in isolated CD34 + cells under control conditions (Erickson et al, ). Remarkably, Runx1 transcription in these cells was significantly enhanced in response to short‐term treatment with purified Wnt3a (4 h) and again the effect was mainly observed at the P1 promoter and paralleled by the transcriptional activity of Wnt/β‐catenin target genes (Fig.…”
Section: Resultssupporting
confidence: 55%
“…A), since they resemble normal HSCs (Engelhardt et al, ). As it has been described, low levels of endogenous Runx1 mRNA were observed in isolated CD34 + cells under control conditions (Erickson et al, ). Remarkably, Runx1 transcription in these cells was significantly enhanced in response to short‐term treatment with purified Wnt3a (4 h) and again the effect was mainly observed at the P1 promoter and paralleled by the transcriptional activity of Wnt/β‐catenin target genes (Fig.…”
Section: Resultssupporting
confidence: 55%
“…Among these factors, GATA‐2, SCL and AML1 have been shown to be indispensable for early haematopoiesis at the stem cell level by both in vivo and in vitro study (Tsai et al , 1994; Okuda et al , 1996; Porcher et al , 1996). Furthermore, it has been shown that these factors are expressed in stem cells in the adult haematopoietic system (Mouthon et al , 1993; Erickson et al , 1996). Therefore, it is possible that changes in the expression level of these factors may lead to an aberrant proliferation and differentiation of stem cells, and may be partly responsible for developing stem cell diseases such as aplastic anaemia.…”
mentioning
confidence: 99%
“…Although ETO contains a zinc finger motif and appears to be the mammalian homologue of the Drosophila gene nervy, 11 no direct DNAbinding activity has been detected, nor has its function been identified. 12 Transcriptional regulation by AML1 through the enhancer core motif has been shown to be important for the tissue specific expression of a number of hematopoietic specific genes including interleukin-3 (IL-3), 13 granulocyte-macrophage colonystimulating factor (GM-CSF), 14 the receptor for CSF-1 (CSF-1R), 15 myeloperoxidase, 16 and subunits of the T-cell antigen receptor (TCR). 8,17 By creating mice deficient in AML1/CBF␤, we 18 as well as others [19][20][21] have shown that the AML1/CBF␤ transcription factor complex is essential for the establishment of definitive hematopoiesis.…”
mentioning
confidence: 99%